2002
DOI: 10.1016/s0092-8674(02)00617-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrating mRNA Processing with Transcription

Abstract: transferase activities are part of the same polypeptide University of Oxford at the N terminus and C terminus, respectively, while South Parks Road in yeast they are catalyzed by separate enzymes. This Oxford OX1 3RE initial cap structure is then recognized by the cap bind-United Kingdom ing complex (CBC), which contains two proteins, CBP20 and CBP80. Upon export through the nuclear pore complex, the nuclear cap binding proteins are replaced by The messenger RNA processing reactions of capping, the cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
750
1
20

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 943 publications
(792 citation statements)
references
References 81 publications
21
750
1
20
Order By: Relevance
“…Interestingly, RNPS1 also interacts with the largest subunit of RNA polymerase II. It was shown that the phosphorylation of the CTD of RNA polymerase also plays a role in posttranscriptional mRNA processing (Proudfoot et al, 2002). The RNA polymerase multiprotein complex also harbours cdk11, which is a cyclin-dependent kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, RNPS1 also interacts with the largest subunit of RNA polymerase II. It was shown that the phosphorylation of the CTD of RNA polymerase also plays a role in posttranscriptional mRNA processing (Proudfoot et al, 2002). The RNA polymerase multiprotein complex also harbours cdk11, which is a cyclin-dependent kinase.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not surprising that increased gene expression occurs with enhanced mRNA processing, since proteins that catalyze polyadenylation are associated with RNA polymerase II (Pol II), providing a link between transcription and formation of the 3 0 end of mRNA (Maniatis and Reed, 2000;Proudfoot et al, 2000). A functional polyadenylation signal terminates transcription and release Pol II (Whale and Ruegsegger, 1999;Shatkin and Manley, 2000), although polyadenylation seems to continue post-transcriptionally (Osheim et al, 1999(Osheim et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…(19) Many pre-mRNAs are spliced before transcription is completed; this cotranscriptional splicing probably plays an important role in ensuring the accuracy of splicing. In cotranscriptional splicing, the evidence suggests that the splicing machinery is physically associated with the RNA synthesis machinery (RNA polymerase and its associated factors).…”
Section: Why So Many Proteins?mentioning
confidence: 99%